Peran Manajemen Administrasi Pendidikan dalam Kemajuan Madrasah Aliyah di Yayasan Ar-Rusdiny NW Segaet - Gapari, Muhamad Zaril (ARZUSIN, 2024)
The management of all institutional interests with an administrative bent is known as administrative management. Every institution or organization has functional activities that are carried out to accomplish specific objectives. A foundation is a type of legal organization that is significant in many facets of society. With a variety of goals, the foundation develops and launches social, educational, humanitarian, cultural, and environmental projects. Thus, administrative management's contribution to an institution's advancement The objectives of this study were to: 1) ascertain the function of administrators in the advancement of madrasahs, and 2) ascertain the contribution of school administration to the advancement of madrasahs. One kind of study that is carried out is qualitative descriptive research. Techniques for gathering data include observations, interviews, and documentation. The MA students, teachers, and principal were the focus of this study. Ar-Rusydiny NW Segaet. According to the study's findings, MA Ar-Rusydiny NW The execution of administrative personnel training and administration-related activities demonstrates how effectively Segaet has managed its operations.